A new (propylphenyl)bibenzyl from Eria bambusifolia. Issue 15 (2nd August 2016) - Zhan, Rui; Zhang, Yan; Chen, Lijun; Chen, Yegao
Abstract: A new (propylphenyl)bibenzyl, bambusifolol (1 ), along with six known compounds, batatasin III (2 ), tristin (3 ), 3-hydroxy-5-methoxy bibenzyl (4 ), gigantol (5 ), 3′, 5-dimethoxy-9, 9′-diacetyl-4, 7′-epoxy-3, 8′-bilign-7-ene-4′-methol (6 ) and balanophonin (7 ) were isolated from the whole plants of Eria bambusifolia . Their structures were elucidated by the means of extensive spectroscopic analysis.3 –7 were isolated from the genus Eria for the first time and2 obtained originally from E. bambusifolia . All the compounds isolated were evaluated for their cytotoxicity against human tumour HL-60, SMMC-7721, A-549, MCF-7 and SW-480 cell lines, but none showed significant activity. Abstract :